Implementation of the Perinatal Death Surveillance and Response guidelines: Lessons from annual health system strengthening interventions in the Rwenzori Sub‐Region, Western Uganda - Enos Mirembe Masereka; Amelia Naturinda; Alex Tumusiime; Clement Munguiko (Wiley, 2020)
Abstract Aim To determine the health facility‐based perinatal mortality rate, its causes and avoidable factors using the perinatal mortality surveillance and response guidelines. Design This was an action study conducted in one of the districts in Western Uganda from 1 January-31 December 2019. Methods A total of 20 perinatal death cases were recruited consecutively. Data were collected using a Ministry of Health Perinatal Death Surveillance and Response (PDSR) questionnaire containing questions on pregnancy, delivery and immediate postnatal care. We used descriptive statistics to describe key data elements. Results We found a health facility‐based perinatal mortality rate of 17.3 deaths per 1,000 live births. Birth asphyxia was the most common cause of perinatal deaths. Seven, three and ten mothers delayed seeking, reaching and receiving appropriate health care, respectively.